Immunogenicity and Vaccine Potential of InsB, an ESAT-6-Like Antigen Identified in the Highly Virulent Mycobacterium tuberculosis Beijing K Strain - Kim, Woo Sik; Kim, Hongmin; Kwon, Kee Woong; Cho, Sang-Nae; Shin, Sung Jae (Frontiers in Microbiology, 2019)
Our group recently identified InsB, an ESAT-6-like antigen belonging to the Mtb9.9 subfamily within the Esx family, in the Mycobacterium tuberculosis Korean Beijing strain (Mtb K) via a comparative genomic analysis with that of the reference Mtb H37Rv and characterized its immunogenicity and its induced immune response in patients with tuberculosis (TB). However, the vaccine potential of InsB has not been fully elucidated. In the present study, InsB was evaluated as a subunit vaccine in comparison with the most well-known ESAT-6 against the hypervirulent Mtb K. Mice immunized with InsB/MPL-DDA exhibited an antigen-specific IFN-γ response along with antigen-specific effector/memory T cell expansion in the lungs and spleen upon antigen restimulation. In addition, InsB immunization markedly induced multifunctional Th1-type CD4+ T cells coexpressing TNF-α, IL-2, and IFN-γ in the lungs following Mtb K challenge. Finally, we found that InsB immunization conferred long-term protection against Mtb K comparable to that conferred by ESAT-6 immunization, as evidenced by a similar level of CFU reduction in the lung and spleen and reduced lung inflammation. These results suggest that InsB may be an excellent vaccine antigen component for developing a multiantigenic Mtb subunit vaccine by generating Th1-biased memory T cells with a multifunctional capacity and may confer durable protection against the highly virulent Mtb K.